Using modified early warning score to predict need of lifesaving intervention in adult non-trauma patients in a tertiary state hospital - Peng, Leong Shian (SAGE Publications, 2018)
Background: Modified early warning score has been validated in many uses in the emergency department. We propose that the modified early warning score performs well in predicting the need of lifesaving interventions in the emergency department, as a predictor of patients who are critically ill. Objective: The study aims to evaluate the use of modified early warning score in sorting out critically ill patients in the emergency department. Methods: The patients’ demographic data and first vital signs (blood pressure, heart rate, temperature, respiratory rate, and level of consciousness) were collected prospectively. Individual modified early warning score was calculated. The outcome was a patient received one or more lifesaving interventions toward the end of stay in emergency department. Multivariate logistic regression analysis was utilized to assess the association between modified early warning score and other potential predictors with outcome. Results: There are a total of 259 patients enrolled into the study. The optimal modified early warning score in predicting lifesaving intervention was ≥4 with a sensitivity of 95% and specificity of 81%. Modified early warning score ≥4 (odds ratio = 96.97, 95% confidence interval = 11.82-795.23, p < 0.001) was found to significantly increase the risk of receiving lifesaving intervention in the emergency department. Conclusion: Modified early warning score is found to be a good predictor for patients in need of lifesaving intervention in the emergency department.